The effect of combinations of sourdough lactic acid bacteria and yeasts on wheat bread quality: Evaluation in terms of microbiological, rheological, textural and volatile components - Alkay, Z.; Durak, M. Z. (PLAPIQUI(UNS-CONICET), 2024)
In this study, the effect of co-cultivation of lactic acid bacteria (Lactiplantibacillus plantarum 45MK-30, and Pichia membranifaciens 11G-11) on the quality of sourdough bread was studied. Two different fermentation phases were used (I and II) and bread making was carried out in the II phase of fermentation. Microbiological analysis, pH and TTA values were checked in these two phases. While cell density and pH value of microorganisms were close to each other in I phase fermentation, a decrease in these values was observed in II phase fermentation. When the rheological analyzes of the doughs at the end of phase II are examined, all doughs exhibited lower elastic behavior. It can be said that the textural feature of sourdough breads is softer compared to both controlled acidified (CA) bread and non-sourdough (flat dough, CY) bread. Another parameter examined in breads was the evaluation of volatile components by HS-GC / MS. It was observed that breads produced by co-cultivation had more volatile components than plain dough bread.
Keywords: LAB; Yeast; Microbial interactions; Bread; STARTER CULTURE; FERMENTATION; AROMA; OPTIMIZATION; Engineering